Functional characterization of three flavonol synthase genes from Camellia sinensis Roles in flavonol accumulation - Jiang, Xiaolan (Plant science : an international journal of experimental plant biology, 2020)
Copyright © 2020 Elsevier B.V. All rights reserved.